Retrotransposon-Adenovirus Hybrid Vectors: Efficient Delivery and Stable Integration of Transgenes via a Two-Stage Mechanism - Soifer, H. S.; Kasahara, N. (Current Gene Therapy, 2004)
It has long been recognized that the mechanisms mediating retrotransposition might be adapted for genomic integration and long-term expression of foreign genes. In particular, long interspersed nuclear elements (LINEs), an abundant class of retrotransposons that are the most active mobile genetic elements in the human genome, have been largely ignored as candidates for development as an integrating vector system because there has been no suitable method for efficiently introducing them into target cells. We have recently developed a LINE-based retrotransposon-adenovirus hybrid vector, in which a helper-dependent adenovirus (HDAd) is utilized as the platform for delivery of a human L1 element and its linked heterologous transgene cassette into the host cell nuclei. While a major drawback to the use of HDAd vectors has been their lack of specific mechanisms to achieve permanent integration into the host genome, the inserted retrotransposon sequences overcome this limitation. The L1-HDAd hybrid thus represents a single vector capable of mediating long-term gene expression by a two-stage mechanism: in the first (adenovirus) stage, the helper-dependent adenovirus serves as a carrier for efficient delivery and transient expression of its encoded L1 / transgene cassette, and in the second (retrotransposon) stage, the L1 retro-element and its associated transgene then permanently integrate into the genome of the adenovirus-transduced cells. We propose that this novel retrotransposon-adenovirus hybrid vector system will be useful both as a vehicle for efficient delivery and long-term stable transduction of therapeutic genes, as well as a tool to elucidate aspects of retrotransposon biology that have previously been difficult to study.
Keywords: ty virus-like particles (ty-vlps)